The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12291-010-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

BMD and Serum Intact Osteocalcin in Postmenopausal Osteoporosis Women

Abstract: India seems to have the highest prevalence of osteoporosis. With growing awareness of osteoporosis and its impact on life span especially in India, special attention is being paid to early detection, management and treatment of postmenopausal osteoporosis in women. Measurement of BMD and osteocalcin are of value in estimating bone turnover rates. The aim of this study is (1) to measure the specific, sensitive bone formation marker such as osteocalcin and BMD in postmenopausal osteoporosis women and postmenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 13 publications
(11 reference statements)
7
42
0
3
Order By: Relevance
“…In osteoporosis, pro-inflammatory cytokines, such as TNF-a, promote osteoclastogenesis and inhibit osteoblastogenesis. Jagtap et al (2011) reported that the mean serum level of osteocalcin was significantly elevated in patients with postmenopausal osteoporosis when compared with that in healthy controls. Moreover, it was reported in a previous study that a mixture containing R. coreanus Miquel and A. membranaceus Bunge extracts helped in the recovery of serum osteocalcin and TNF-a levels in OVX mice (Jung Koo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In osteoporosis, pro-inflammatory cytokines, such as TNF-a, promote osteoclastogenesis and inhibit osteoblastogenesis. Jagtap et al (2011) reported that the mean serum level of osteocalcin was significantly elevated in patients with postmenopausal osteoporosis when compared with that in healthy controls. Moreover, it was reported in a previous study that a mixture containing R. coreanus Miquel and A. membranaceus Bunge extracts helped in the recovery of serum osteocalcin and TNF-a levels in OVX mice (Jung Koo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime risk for women to have an osteoporotic fracture is 30-40% worldwide (1), which has a notable social, physical and economic impact (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In osteoporosis, generally there is a deficiency of calcium and phosphorus level and since osteocalcin is a calcium dependent biomarker and has a strong affinity with bone matrix (hydroxyapatite) responsible for mineralization of bone. Osteoporosis leads to decreased hydroxyapatite crystal formation and hence results in increase in serum osteocalcin levels [8,9].…”
Section: Introductionmentioning
confidence: 99%